1996
DOI: 10.1093/ajcn/64.6.952
|View full text |Cite
|
Sign up to set email alerts
|

Albumin kinetics in edematous and nonedematous protein-energy malnourished children

Abstract: The kinetic changes responsible for decreased plasma albumin and the relation between plasma albumin and the edema of protein-energy malnutrition (PEM) were investigated by measuring the plasma concentration, fractional (FSR) and intravascular absolute (ASR) synthesis rates of albumin in seven edematous and seven nonedematous children with PEM by using constant intragastric infusions of [2H3]leucine. Studies were done 2 d postadmission (study 1), 8 d postadmission (study 2), and at recovery (study 3). In study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 19 publications
4
21
1
Order By: Relevance
“…Consistent with the general finding that younger persons have higher metabolic rates than do adults, a higher albumin FSR, ranging from 15%/d to 20%/d, has been found in 12-mo-old infants (43,44). Bunt et al (21) found values of 14%/d on the first postnatal day in fasted premature infants with a gestational age of 28 wk.…”
Section: Discussionsupporting
confidence: 52%
“…Consistent with the general finding that younger persons have higher metabolic rates than do adults, a higher albumin FSR, ranging from 15%/d to 20%/d, has been found in 12-mo-old infants (43,44). Bunt et al (21) found values of 14%/d on the first postnatal day in fasted premature infants with a gestational age of 28 wk.…”
Section: Discussionsupporting
confidence: 52%
“…Marasmus is defined by clinical wasting, while kwashiorkor is typically accompanied by more complex characteristics such as 21 pitting edema, hair discoloration, skin lesions and hepatomegaly, although considerable overlap with marasmus often exists. Biochemical features typically present in kwashiorkor include hepatic steatosis [34,35], a reduced protein turnover [36] and decreased albumin synthesis [37].…”
Section: Discussionmentioning
confidence: 99%
“…The first measurement was made in the infected-malnourished state ,2 days post-admission (experiment 1), the second when their infections were clear and the oedematous children had lost their oedema, ,8 days post-admission (experiment 2), and the third measurement was performed when the children were fully recovered, ,54 days post-admission (experiment 3). [17][18][19][20] Albumin and transthyretin (TTR)…”
Section: Synthesis Of Plasma Proteinsmentioning
confidence: 99%